2018
DOI: 10.1002/pmh.1410
|View full text |Cite
|
Sign up to set email alerts
|

Differential relations of executive functioning to borderline personality disorder presentations in adolescents

Abstract: Borderline personality disorder (BPD) in adolescents is highly complex and heterogeneous. Within the disorder, research has suggested the existence of at least two subgroups: one with predominantly internalizing psychopathology features and one with predominantly externalizing psychopathology features. One process that may differentiate these groups is executive functioning (EF), given that poor EF is linked to externalizing psychopathology. Against this background, the current study used a multi-informant app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…Under the antagonistic externalizing spectrum, the evidence of cognitive deficits is strong for borderline PD 189,190 , whereas findings concerning narcissistic, histrionic and paranoid PDs are mostly derived from symptom, descriptive and trait checklists 191,192 .…”
Section: Validity Evidencementioning
confidence: 99%
“…Under the antagonistic externalizing spectrum, the evidence of cognitive deficits is strong for borderline PD 189,190 , whereas findings concerning narcissistic, histrionic and paranoid PDs are mostly derived from symptom, descriptive and trait checklists 191,192 .…”
Section: Validity Evidencementioning
confidence: 99%
“…In contrast, the CPT-3 assesses the ability to deliberately withhold a prepotent response (which falls in the domain of action impulsivity), and only about one-third of participants in the current study scored in the clinically elevated range. With this said, at least two studies have shown that subgrouping BPD patients based on profiles of self-reported executive function can lead to the identification of subgroup-specific symptom profiles (Hoermann, Clarkin, Hull, & Levy, 2005;Kalpakci, Ha, & Sharp, 2018) and the prognostic utility of these self-reported measures for predicting treatment outcomes may be investigated in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the confirmation of these neurocognitive alterations in BPD, confirming deficits in memory processes, attention and mainly executive functions (EFs), a specific neuropsychological profile for these patients has not yet been established (López-Villatoro et al 2023;Ruocco et al 2012). According to some authors (Kalpakci, Ha, and Sharp 2015;López-Villatoro et al 2023), this lack of a concrete neuropsychological profile is mainly due to the lack of specificity of many neuropsychological tests and the heterogeneity of the disorder.…”
Section: Introductionmentioning
confidence: 99%